Hooper humperdink . . . ? not him - LeSieg, Theo (New York : Random House, 1976)
A youngster plans a huge, spectacular party, inviting friends whose names begin with every letter from A to Z - exept for one person
Keywords: Stories in rhyme; Alphabet books; Parties -- Fiction